Effectiveness of sarcopenia screening indicators in predicting death in older patients with chronic heart failure - Zhouyu Li; Sha Huang; Xia Lin; Yukuan Xie; Yan Xia; Xiaoyan Chen (BMC Geriatrics)
Abstract Objective This study investigated the associations between multiple sarcopenia screening indicators and the risk of mortality, both overall and within 30 days of discharge, in older patients with chronic heart failure (CHF). Materials and methods This retrospective study enrolled inpatients aged ≥ 60 years diagnosed with CHF in a teaching hospital in western China. The general data of the patients between January 1, 2017 and July 7, 2022 were collected from the electronic medical record system, and information on mortality was obtained through telephonic follow-up from July 31, 2022 to August 1, 2022. Cox regression analysis was used to explore the possible association between sarcopenia screening indicators, including the serum creatinine (Cr)/cystatin C (CysC)*100 and AST/ALT ratios, as well as the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR), and risk of mortality, both overall and within 30 days of discharge. Results This study included 482 older patients with CHF, including 270 males (56.02%) and 169 patients (35.06%) who died. After adjustment for possible confounding factors, Cox regression analysis showed that compared with patients with PLR<125.11, those with PLR ≥ 125.11 had a higher risk of death within 30 days after discharge (HR = 3.75, 95% CI:1.09–12.94) as well as overall mortality (HR=1.82, 95%CI: 1.14–2.93). However, Cr/CysC*100, AST/ALT, and NLR were not associated with either overall or 30-day mortality risk. Conclusion The PLR was found to be associated with the risk of both overall mortality and death within 30 days of discharge in older patients with CHF.